Декодування трьох типів австрійських архівних записів про середньовічні скарби на території Північної Буковини - Огуй, О. (Спеціальні історичні дисципліни: питання теорії та методики, 2007)
This article deals with three kinds of Austrian archive entrees about found coin hoards (without nominal; with only money evaluation; without quantity of coins). Author offers to use adequate ways of their reinterpretation on the basis of approximate-statistic calculations (due to the common weights and evaluations of found hoards).